Degradation kinetics and formation of regulated and emerging disinfection by-products during chlorination of two expectorants ambroxol and bromhexine. (15th May 2023) - Wang, Wuming; Zhou, Zichong; Ding, Shunke; Yang, Wenyuan; Jin, Wei; Chu, Wenhai; Xu, Zuxin
Highlights: The second order reaction kinetics constant between chlorine and AMB/BRO were determined. 2-chloro-4, 6-dibromoaniline and 2, 4, 6-tribromoaniline were firstly identified as emerging DBPs. Brominated DBP yields from AMB/BRO were much higher than natural organic matter. Bromine in brominated organic compounds could significantly enhance brominated DBP formation. Abstract: Ambroxol hydrochloride (AMB) and bromhexine hydrochloride (BRO) are classic expectorants and bronchosecretolytic pharmaceuticals. In 2022, both AMB and BRO were recommended by medical emergency department of China to alleviate cough and expectoration for symptoms caused by COVID-19. The reaction characteristics and mechanism of AMB/BRO with chlorine disinfectant in the disinfection process were investigated in this study. The reaction of chlorine with AMB/BRO were well described by a second-order kinetics model, first-order in both AMB/BRO and chlorine. The second order rate reaction constant of AMB and BRO with chlorine at pH 7.0 were 1.15 × 10 2 M −1 s −1 and 2.03 × 10 2 M −1 s −1, respectively. During chlorination, a new class of aromatic nitrogenous disinfection by-products (DBPs) including 2-chloro-4, 6-dibromoaniline and 2, 4, 6-tribromoaniline were identified as the intermediate aromatic DBPs by gas chromatography-mass spectrometry. The effect of chlorine dosage, pH, and contact time on the formation of 2-chloro-4, 6-dibromoaniline and 2, 4, 6-tribromoaniline were evaluated. In addition, it was found that bromine in AMB/BRO were vital bromine source to greatly promote the formation of classic brominated DBPs, with the highest Br-THMs yields of 23.8% and 37.8%, respectively. This study inspired that bromine in brominated organic compounds may be an important bromine source of brominated DBPs. Graphical abstract: Image, graphical abstract